DEVELOPMENT OF INFORMATION TECHNOLOGY-BASED LEARNING MEDIA FOR EDUCATORS IN ELEMENTARY SCHOOLS - Sa'diyah; Chairul Anwar; Muwahidah Nurhasanah; Ida Aflaha, Dwi Sari; Handayani, Suci (LP2M IAI Al-Khairat Pamekasan, 2023)
This research aims to determine whether instructional media can be used to share learning messages and data. Students will better understand and understand the material in a well-designed learning environment. The learning environment is also increasingly advanced in the information and globalization era. Learning to use information technology (IT) is a must. Media functions in the learning process as a teaching tool and as a source of information and news. Each learning environment has advantages and disadvantages. Therefore, the use of the learning environment must be adequately planned. The learning environment is growing in the current information and globalization era. There is an argument that using information technology (IT) as a learning method is necessary.